2018
DOI: 10.1175/bams-d-17-0204.1
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Thermodynamic Observations in Convective Storms from Balloonborne Probes Acting as Pseudo-Lagrangian Drifters

Abstract: The severe storms research community lacks reliable, aboveground, thermodynamic observations (e.g., temperature, humidity, and pressure) in convective storms. These missing observations are crucial to understanding the behavior of both supercell storms (e.g., the generation, reorientation, and amplification of vorticity necessary for tornado formation) and larger-scale (mesoscale) convective systems (e.g., storm maintenance and the generation of damaging straight-line winds). This paper describes a novel way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…18-4; Stout and Huff 1953). Although the physical processes the hook echo represented were not fully understood at the time (Markowski 2002), the frequent association between the feature and tornadoes was adopted as an important part of the process of very short-term forecasts of tornado threat (known as warnings) in the United States.…”
Section: The Post-world War II Era: Radar and The Development Of Forementioning
confidence: 99%
See 3 more Smart Citations
“…18-4; Stout and Huff 1953). Although the physical processes the hook echo represented were not fully understood at the time (Markowski 2002), the frequent association between the feature and tornadoes was adopted as an important part of the process of very short-term forecasts of tornado threat (known as warnings) in the United States.…”
Section: The Post-world War II Era: Radar and The Development Of Forementioning
confidence: 99%
“…Surface observations collected by mobile vehicles during VORTEX and subsequent smaller projects allowed Markowski et al (2002) to examine the thermodynamic conditions near low-level mesocyclones, some of which produced tornadoes and some of which did not. This work tested hypotheses that had been developed by numerical modeling of conditions needed for strong low-level rotation and found that the observations showed much less cooling than models.…”
Section: 10mentioning
confidence: 99%
See 2 more Smart Citations
“…During the Rivers of Vorticity in Supercells (RiVorS) project in May 2017, Markowski et al [10] used ground-launched PLDs for thermodynamic measurements in supercells. Using ground-level inflows, the team was able to target the supercell forward flank region successfully.…”
Section: Introductionmentioning
confidence: 99%